Pengaruh Substitusi Tepung Tapioka dengan Tepung Singkong (Manihot esculenta) terhadap Mutu Organoleptik Bakso Ayam - Hendrik, Hendrik; Lunatri, Andi (Fakultas Peternakan Universitas Madako Tolitoli, 2024)
This study aimed to determine the effect of substituting tapioca flour with cassava flour on the organoleptic quality of chicken meatballs. The experiment was conducted using a Completely Randomized Design (CRD) consisting of 5 treatments and 4 replications. The treatments were substitution levels of tapioca flour with cassava flour, namely A = 0% (control), B = 25%, C = 50%, D = 75%, and E = 100%. The parameters observed included organoleptic tests covering color, taste, aroma, and texture, which were evaluated by semi-trained panelists using a hedonic scale. The results showed that cassava flour substitution had a significant effect on the organoleptic quality of chicken meatballs. The treatment with a 50% substitution level (C) obtained the highest scores across all parameters, particularly in texture and chewiness, and was preferred compared to other treatments. Substitution levels above 75% tended to decrease the organoleptic quality, producing a coarser texture and a less desirable aroma. Therefore, the use of cassava flour as a tapioca substitute up to a level of 50% can be applied as an economical alternative raw material while maintaining the organoleptic quality of chicken meatballs.